2017
DOI: 10.1242/dev.150458
|View full text |Cite
|
Sign up to set email alerts
|

Human organomics: a fresh approach to understanding human development using single-cell transcriptomics

Abstract: Innovative methods designed to recapitulate human organogenesis from pluripotent stem cells provide a means to explore human developmental biology. New technologies to sequence and analyze single-cell transcriptomes can deconstruct these 'organoids' into constituent parts, and reconstruct lineage trajectories during cell differentiation. In this Spotlight article we summarize the different approaches to performing single-cell transcriptomics on organoids, and discuss the opportunities and challenges of applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Recent advances in single-cell transcriptomics have made it possible to monitor cell-type-specific transcriptional processes, such as lineage progression during organ development or tissue homeostasis, within complex tissues at unprecedented resolution (Camp and Treutlein, 2017;Sandberg, 2014;Tanay and Regev, 2017). Here, we combined lineage tracing of Lgr5-or Lgr6-expressing SCs with single-cell transcriptome analyses of thousands of individual cells to capture the molecular adaptation of SC progeny from different niches during wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in single-cell transcriptomics have made it possible to monitor cell-type-specific transcriptional processes, such as lineage progression during organ development or tissue homeostasis, within complex tissues at unprecedented resolution (Camp and Treutlein, 2017;Sandberg, 2014;Tanay and Regev, 2017). Here, we combined lineage tracing of Lgr5-or Lgr6-expressing SCs with single-cell transcriptome analyses of thousands of individual cells to capture the molecular adaptation of SC progeny from different niches during wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the generation of tissue-specific organoids has been suggested to be important in the modelling of cell–cell interactions in the three-dimensional level during organ development 47 . Koehler et al 48 reported the generation of inner ear organoids from human ESCs and iPSCs and demonstrated that inner ear organoids can have sensory epithelial cells due to the expression of HC markers, such as ESPN and MYO7A.…”
Section: Discussionmentioning
confidence: 99%
“…These methods make use of a differential expression of fluorophore combinations or other cell barcoding techniques. As to brain organoids, these approaches of cell lineage tracing could constitute a vital experimental avenue to confirm and complement in silico lineage analyses derived from single-cell sequencing (Camp and Treutlein, 2017;Camp et al, 2018). A significant advance in this context would be the transcriptomic analysis of defined cell subpopulations with an identified location within brain organoids, labeled via lineage-specific expression of fluorescent proteins.…”
Section: Outlook and Future Applicationsmentioning
confidence: 99%